Knowledge, attitude, prior exposure and intention to breastfeed among undergraduate university students / Syahrul Bariah Abdul Hamid and Nabilah Yahya - Abdul Hamid, Syahrul Bariah; Yahya, Nabilah (Universiti Teknologi MARA Cawangan Selangor, 2018)
The Theory of Planned Behaviour by Ajzen (1985) states that breastfeeding intention which is made prior to pregnancy predicted future breastfeeding outcomes and also influenced by factors including attitude, knowledge and exposure. The goal of this study was to investigate the level of breastfeeding knowledge, attitude, prior exposure and intention to breastfeed and the relationship between these factors among non-pregnant, single undergraduates. There are limited studies in Malaysia involving young adults who will be future parents. Methods: This cross-sectional study involved 377 students in UiTM Puncak Alam, Selangor. Self- administered questionnaires adapted from Infant Feeding Knowledge Test and Iowa Infant Feeding Attitude Score (IIFAS) were included as research instruments. Results: Overall study population had a low level of knowledge (10.61±2.10) and attitude (60.64± 5.02) towards breastfeeding, high exposure (2.7±0.52) and intention (4.74±0.64) to breastfeed especially in females. Breastfeeding knowledge is significantly associated with breastfeeding attitude and prior breastfeeding exposure. Breastfeeding intention also established an association with breastfeeding attitude and prior breastfeeding exposure. Subsequent predictive analysis found that breastfeeding attitude impacts breastfeeding intention. Conclusion: Breastfeeding intervention should target undergraduate university students in preparing these future parents with adequate and accurate knowledge and positive attitudes towards breastfeeding thus, resulting in higher breastfeeding intention and greater efforts of initiation and sustenance of breastfeeding.